The International Council of Nurses in the time of the COVID‐19 pandemic. (30th May 2021) - Kennedy, Annette
Abstract : International Council of Nurses President Annette Kennedy reviews the organization's contribution to nursing during the COVID‐19 pandemic. She describes the Council's efforts to support nurses around the world and bring its National Nursing Associations together to share their experiences and best practices, and the lessons learned with other nations who are at different stages of the pandemic.